EVALUASI SENSORI GULA KELAPA SERBUK DENGAN PENAMBAHAN LARUTAN TEMPURUNG KELAPA PADA SAAT PENYADAPAN NIRA - Azhari, Adinda Salwa; Raharjo, Dwi; Hartanti, Lucky (Fakultas Pertanian Universitas Tanjungpura, 2025)
Powdered coconut sugar is a processed product derived from the coconut plant, namely sap through a tapping process that contains various nutrients, making it a good place for microbial growth and must be overcome by using natural ingredients with antimicrobial properties, namely coconut shells. The use of natural ingredients can affect the panelists' assessment. The purpose of this study was to obtain the concentration of coconut shell solution that produces the best sensory characteristics of powdered coconut sugar. The sensory characteristics of powdered coconut sugar observed were color, aroma, sweetness level, and overall preference. The results of the sensory test were analyzed using the Kruskal-Wallis test. The test results showed that the coconut shell solution had a significant effect on color, sweetness level, and overall preference (KW>11.07), but had no significant effect on aroma. The 0 mL/L treatment gave the highest value for color (4.73), while the 15 mL/L coconut shell solution gave the highest value for aroma (3.27), sweetness level (3.83), and overall preference (3.77). Based on these results, a coconut shell solution of 15 mL/L provided the best sensory characteristics and was most preferred by panelists in powdered coconut sugar products.